In vitro antiherpetic activity of a chemically sulfated galactomannan from Leucaena leucocephala seeds - LUCY ONO (São Paulo State University (UNESP), 2010)
A chemically sulfated galactomannan (LLS-2) was obtained, starting from the polysaccharide extracted from seeds of Leucaena leucocephala, which presented 15.2% sulfate and a degree of sulfation of 0.60, and its effect on the replication of Herpes simplex virus 1 (HSV-1) in Vero cells was investigated. LLS-2 showed a 93.7% inhibition of the HSV-1 replication at a concentration of 2.5 micrograms/ml, when added during its adsorption step, evaluated by the plaque reduction method, and a selectivity index higher than 1 000, suggesting that it inhibits the HSV-1 binding to the host cell, but also, in a less significant way, it showed an antiviral effect following the virus attachment step, which indicates that sulfated polysaccharides could act by more than one antiviral mechanism. Keywords: Leucaena leucocephala. Galactomannan. Sulfation. HSV-1; Antiviral activity RESUMO Obteve-se uma galactomanana quimicamente sulfatada (LLS-2) a partir de polissacarídeo extraído de sementes de Leucaena leucocephala, a qual apresentou 15.2% de sulfato e grau de derivatização de 0,60, e, seu efeito antiviral sobre a replicação do vírus Herpes simplex tipo 1 (HSV-1) em células Vero foi avaliado pela metodologia de redução do número de unidades formadoras de placas. LLS-2 apresentou 93.7% de inibição da replicação viral à concentração de 2,5 μg/ml, quando adicionado durante as etapas iniciais de replicação, com um índice de seletividade maior que 1.000, sugerindo que LLS-2 inibe a ligação de HSV-1 às células hospedeiras. Palavras-chave: Leucaena leucocephala. Galactomanana. Sulfatação. HSV-1. Atividade antiviral.